Design, synthesis, molecular docking, and in vitro ?-glucosidase inhibitory activities of novel 3-amino-2,4-diarylbenzo[4,5]imidazo[1,2-a]pyrimidines against yeast and rat ?-glucosidase - Peytam, Fariba; Takalloobanafshi, Ghazaleh; Saadattalab, Toktam; Norouzbahari, Maryam; Emamgholipour, Zahra; Moghimi, Setareh; Foroumadi, Alireza (Nature Portfolio, 2021)
In an attempt to find novel, potent alpha-glucosidase inhibitors, a library of poly-substituted 3-amino-2,4-diarylbenzo[4,5]imidazo[1,2-a]pyrimidines 3a-ag have been synthesized through heating a mixture of 2-aminobenzimidazoles 1 and alpha-azidochalcone 2 under the mild conditions. This efficient, facile protocol has been resulted into the desirable compounds with a wide substrate scope in good to excellent yields. Afterwards, their inhibitory activities against yeast alpha-glucosidase enzyme were investigated. Showing IC50 values ranging from 16.4 +/- 0.36 mu M to 297.0 +/- 1.2 mu M confirmed their excellent potency to inhibit alpha-glucosidase which encouraged us to perform further studies on alpha-glucosidase enzymes obtained from rat as a mammal source. Among various synthesized 3-amino-2,4-diarylbenzo[4,5]imidazo[1,2-a]pyrimidines, compound 3k exhibited the highest potency against both Saccharomyces cerevisiae alpha-glucosidase (IC50=16.4 +/- 0.36 mu M) and rat small intestine alpha-glucosidase (IC50=45.0 +/- 8.2 mu M). Moreover, the role of amine moiety on the observed activity was studied through substituting with chlorine and hydrogen resulted into a considerable deterioration on the inhibitory activity. Kinetic study and molecular docking study have confirmed the in-vitro results.
Keywords: Efficient Synthesis; Biological Evaluation; Vinyl Azides; Derivatives; Potent; Catalyst; Identification; Anticancer; Annulation; Pyridines